Effects of Treatment Setting on Outcomes of Flexibly-Dosed Intensive Cognitive Behavioral Therapy for Pediatric OCD: A Randomized Controlled Pilot Trial - Selles, Robert R.; Naqqash, Zainab; Best, John R.; Franco-Yamin, Diana; Qiu, Serene T.; Ferreira, Jessica S.; Deng, Xiaolei; Hannesdottir, Dagmar Kr.; Oberth, Carla; Belschner, Laura; Negreiros, Juliana; Farrell, Lara J.; et al. (Frontiers in Psychiatry, 2021)
Introduction: Optimizing individual outcomes of cognitive-behavioral therapy (CBT) remains a priority. Trial Registration: ClinicalTrials.gov NCT03672565; https://clinicaltrials.gov/ct2/show/NCT03672565 Methods: Youth were randomized to receive intensive CBT at a hospital clinic (n = 14) or within their home (n = 12). Youth completed 3x3 hour sessions (Phase I) and up to four additional 3-hour sessions as desired/needed (Phase II). An independent evaluator assessed youth after Phase I, Phase II (when applicable), and at 1- and 6-months post-treatment. A range of OCD-related (e.g., severity, impairment) and secondary (e.g., quality of life, comorbid symptoms) outcomes were assessed. Results: Families’ satisfaction with the treatment program was high. Of study completers (n = 22), five youth (23%) utilized no Phase II sessions and 9 (41%) utilized all four (Median Phase II sessions: 2.5). Large improvements in OCD-related outcomes and small-to-moderate benefits across secondary domains were observed. Statistically-significant differences in primary outcomes were not observed between settings; however, minor benefits for home-based treatment were observed (e.g., maintenance of gains, youth comfort with treatment). Discussion: Intensive CBT is an efficacious treatment for pediatric OCD. Families opted for differing doses based on their needs. Home-based treatment, while not substantially superior to hospital care, may offer some value, particularly when desired/relevant.